2021
DOI: 10.1186/s13049-021-00858-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous versus intravenous vascular access during cardiopulmonary resuscitation for out-of-hospital cardiac arrest: a systematic review and meta-analysis of observational studies

Abstract: Introduction This study is aimed to investigate the association of intraosseous (IO) versus intravenous (IV) route during cardiopulmonary resuscitation (CPR) with outcomes after out-of-hospital cardiac arrest (OHCA). Methods We systematically searched PubMed, Embase, Cochrane Library and Web of Science from the database inception through April 2020. Our search strings included designed keywords for two concepts, i.e. vascular access and cardiac arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“… 6 To date, studies comparing the clinical-effectiveness of the IO and intravenous (IV) drug routes are limited to observational research. 6 , 7 , 8 These studies consistently show that the IO route, is associated with similar or worse outcomes. However, the findings of these observational studies are challenging to interpret in the context of important residual confounding and resuscitation time bias.…”
Section: Introductionmentioning
confidence: 66%
“… 6 To date, studies comparing the clinical-effectiveness of the IO and intravenous (IV) drug routes are limited to observational research. 6 , 7 , 8 These studies consistently show that the IO route, is associated with similar or worse outcomes. However, the findings of these observational studies are challenging to interpret in the context of important residual confounding and resuscitation time bias.…”
Section: Introductionmentioning
confidence: 66%
“…Retrospective studies in humans demonstrated a time advantage of IO vs. IV access [ 22 , 23 ], while non-inferiority studies failed to find a significant disadvantage of IO access for clinical outcomes [ 24 ]. A current systematic review [ 25 ], investigating the effects of venous access type on neurological outcome and survival in OHCA, reported no difference between IV and IO access in the pooled analysis of nine observational studies after correcting for time between cardiac arrest and drug administration. Another systematic review [ 26 ], comparing IV and IO routes during cardiac arrest, found limited evidence in favor of IV administration in observational studies and no effect in the subgroup analyses of the randomized controlled trials reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited knowledge on the effect of administration site and the outcomes “survival” or “favourable neurological outcome”. Reports from several clinical studies vary with findings of both similar outcomes regardless of access route 39 41 and differing outcomes 16 19 , 42 , 43 when comparing intraosseous drug delivery and intravenous drug delivery in OHCA patients.…”
Section: Discussionmentioning
confidence: 99%